2012
DOI: 10.1002/zaac.201200308
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Organic Species and Oxoanion in the Synthesis of two Uranyl Sulfate Hydrates, (H3O)2[(UO2)2(SO4)3­(H2O)]·7H2O and (H3O)2[(UO2)2(SO4)3(H2O)]·4H2O, and a Uranyl Selenate‐Selenite [C5H6N][(UO2)(SeO4)(HSeO3)]

Abstract: Two uranyl sulfate hydrates, (H 3 O) 2 [(UO 2 ) 2 (SO 4 ) 3 -(H 2 O)]·7H 2 O (NDUS) and (H 3 O) 2 [(UO 2 ) 2 (SO 4 ) 3 (H 2 O)]·4H 2 O (NDUS1), and one uranyl selenate-selenite [C 5 H 6 N][(UO 2 )(SeO 4 )-(HSeO 3 )] (NDUSe), were obtained and their crystal structures solved.NDUS and NDUSe result from reactions in highly acidic media in the presence of l-cystine at 373 K. NDUS crystallized in a closed vial at 278 K after 5 days and NDUSe in an open beaker at 278 K after 2 weeks. NDUS1 was synthesized from aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The diversity of polyhedral units found in uranyl compounds is unique, starting from isolated complexes [1][2][3] and clusters [4][5][6][7] to cage compounds [8][9][10][11] and nanotubules [12][13][14]. Selenium-containing uranyl oxysalts are known for both monoand divalent inorganic cations [15][16][17][18][19], as well as for organic template molecules of various charge and structure [20][21][22][23][24]. The crystal structures of uranyl selenates and selenites are based upon a variety of complex units formed by polymerization of U and Se coordination polyhedra.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of polyhedral units found in uranyl compounds is unique, starting from isolated complexes [1][2][3] and clusters [4][5][6][7] to cage compounds [8][9][10][11] and nanotubules [12][13][14]. Selenium-containing uranyl oxysalts are known for both monoand divalent inorganic cations [15][16][17][18][19], as well as for organic template molecules of various charge and structure [20][21][22][23][24]. The crystal structures of uranyl selenates and selenites are based upon a variety of complex units formed by polymerization of U and Se coordination polyhedra.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of aqueous and solvothermal reactions to produce uranyl compounds have been previously reported that utilize cyclic cations as templating agents. [26][27][28][29][30] However, there are few studies that examine the use of ionic liquids as both solvent and templating agent for the synthesis of uranyl compounds. Specifically, we are interested in the effects the ionothermal technique may have on the isolation of uranyl structural units that commonly form in aqueous solution.…”
Section: Discussionmentioning
confidence: 99%
“…20 Sulfates of U(IV) examined include the neutral complex U(SO 4 ) 21 Reactions of uranyl acetate with oleum has given two forms of UO 2 (S 2 O 7 ), as well as UO 2 (HSO 4 ) 2 and U(SO 4 ) 2 , the latter by reaction (and reduction) at 300 1C. 22 Other uranyl sulfates characterised include ( 23 DFT-based molecular dynamics simulations have been applied to uranium aqua ions, indicating 8-9 bound waters for U 4+ (aq) and 5 bound waters for UO 2 n+ (n = 1, 2). 24 Calculation indicates that UO 2 Cl 2 is a weaker Lewis acid than free UO 2 2+ .…”
Section: Complexesmentioning
confidence: 99%